Answer:
Look at the step-by-step explanation below
Explanation:
The first thing to do is do inverse operations and add 3 to both sides
(3 + 5 = 2x -3 + 3)
The positive 3 and negative 3 will cancel out on the right. Your equation should now look like.
(8 = 2x)
The next step is to divide 2 from both sides. This is because 2x is multiplication. (2)(x) And the opposite of multiplication is division. Your equation should look like this
(8/2 = 2x/2)
Now cancelling out the 2's on the right and dividing 8 by 2 you would get...
(4 = x)